Valuing a business : - Pratt, Shannon P. (McGraw Hill, 2008)
Written by Shannon Pratt, one of the world's leading authorities on business valuation, this updated classic offers a complete “one-stop” compendium of information on the full range of valuation concepts and methods. This landmark reference also presents a wealth of recent court cases for each valuation area, which together provide a comprehensive overview of all the legal rulings and trends in the field of business valuation.